Culpable Media: Digital Disembodiment and the Rise of “Crowdsourced Morality” - Ryasvy, Wayne Erik (AoIR Selected Papers of Internet Research, 2013)
Social media encourage collective practices of public expression and individualized practices of privacy and reputation management. Juxtaposing three contemporary extreme scenario case studies, future select interviews with first-year college students and HR staff, and the historic practices of impression management and public expression, I contend that users participate in collective expression and surveillance through social media that ultimately culminate in an extensive and potentially threatening form of disembodiment as it subjects ‘culpable’ individuals to the morality of the crowd. In this process of “crowdsourced morality,” users not only strip expressions of original context and intent, but they also bully ‘culpable’ individuals by grossly mischaracterizing them to incite public censure and punishment. Therefore, while social media theoretically promote expression through shared connections and content, they also operate as culpable media that complicate personal expression by producing power differentials that always potentially disempower the individual against the excruciating power of the crowd.